Promoting Cassava Productivity in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Claude M. Fauquet, Director GCP2 - Global Cassava Partnership for the 21st Century - Sharing views on the importance of building partnerships and networks to promote Cassava Productivity in Africa. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/